Islamization of Science - REHAF A. MADANI (International Journal of Islamic Thought, 2016)
The Islamization of Knowledge process is considered as one of the most important and intellectual movements of the 20ih century. It is also one of the most credible and long-standing contemporary Muslim intellectual responses towards modernism. The un-defined structure and framework of the Islamization process makes it a challenging task and recognized more as a theory rather than effective methodology plan. This paper focuses on the Islamization of Knowledge in general, comprising with its history, definition and pioneers. Moreover, Islamization of science subjects in specific with the objective of introducing a framework for this phenomenon, based on Al-Farouqi’s 12-step work-plan and Berghout’s framework using a descriptive theoretical theory.